Metabolomic Profiles of Plasma Retinol-Associated Dyslipidemia in Men and Women - Wang, Ninglin; Ru, Yuan; Yang, Zhiying; Sun, Changxuan; Li, Shanshan; Min, Yan; Zhao, Xueyin; Lu, Ying; Hsing, Ann W.; Zhu, Shankuan (Frontiers in Nutrition, 2021)
Background & aims: Studies in both animals and humans show that a high intake of vitamin A is associated with a lower risk of dyslipidemia. However, the association of plasma retinol levels with dyslipidemia is unclear. Therefore, the aim of this study was to investigate the association of plasma retinol and dyslipidemia and to identify the related metabolites and pathways in a general population. Methods: We included 250 participants aged 20 to 80 years from the Wellness Living Laboratory China cohort. Associations between plasma retinol levels and dyslipidemia were analyzed using adjusted logistic models. Related metabolites were identified using ANCOVA, adjusted for the false discovery rate, and were used for pathway analyses. Because there are sex differences in plasma retinol levels, all analyses were conducted separately by sex. Results: Plasma retinol was significantly higher in men than in women. A positive association between plasma retinol and dyslipidemia was found in both sexes. In men, the 2nd and 3rd tertiles showed significantly higher proportions of dyslipidemia than the 1st tertile (1st tertile vs. 2nd tertile: p=0.026; 1st tertile vs. 3rd tertile: p=0.003). In women, the 3rd tertile showed a significantly higher proportion of dyslipidemia than the 1st and 2nd tertiles (3rd tertile vs. 1st tertile: p=0.002, 3rd tertile vs. 2nd tertile: p=0.002). Overall, 75 and 30 metabolites were significantly associated with retinol levels in men and women, respectively. According to these metabolites, lipid metabolic pathways including glycerophospholipid, arachidonic acid, linoleic acid, alpha-linolenic acid, and glycosylphosphatidylinositol, as well as steroid hormone biosynthesis pathways were found to overlap across sexes. These pathways showed that elevated retinol levels might be associated with hormone metabolism and inflammation status. Conclusions: We found a positive association between plasma retinol levels and dyslipidemia. The related metabolomics profiles and interrupted pathways showed that such an increase might be associated with steroid hormone synthesis and inflammation. Further large, population-based longitudinal studies and intervention studies are needed to confirm the role of retinol in lipid metabolism and the prevention of cardiovascular disease. Keywords: Vitamin A, Plasma retinol, Dyslipidemia, Metabolomics profiles, Pathway analysis